GABA enzymatic assay kit. Issue 1 (2nd January 2020) - Nishiyama, Tatsuya; Sulistyaningdyah, Woro Triarsi; Ueda, Kenji; Kusakabe, Hitoshi
ABSTRACT: We developed an enzymatic assay system enabling easy quantification of 4-aminobutyric acid (GABA). The reaction of GABA aminotransferase obtained from Streptomyces decoyicus NBRC 13977 was combined to those of the previously developed glutamate assay system using glutamate oxidase and peroxidase. The three-enzyme system allowing GABA-dependent dye formation due to the oxidative coupling between 4-aminoantipyrine and Trinder's reagent enabled accurate quantification of 0.2 − 150 mg/L GABA. A pretreatment mixture consisting of glutamate oxidase, ascorbate oxidase and catalase eliminating glutamate, ascorbate, and hydrogen peroxide, respectively, was also prepared to remove those inhibitory substances from samples. Thus, constructed assay kit was used to measure the GABA content in tomato samples. The results were almost the same as that obtained by the conventional method using liquid chromatography-tandem mass spectrometry. The kit will become a promising tool especially for the on-site measurement of GABA content in agricultural products. Graphical abstract: : Schematic representation of the enzyme quantification system for GABA. Serial reaction catalyzed by the three enzymes enables colorimetric measurement of GABA content in biological samples.